Vibrational spectroscopies for the analysis of cutaneous permeation: experimental limiting factors identified in the case of caffeine penetration - Tfaili, Sana; Gobinet, Cyril; Josse, Gwendal; Angiboust, Jean-François; Baillet, Arlette; Manfait, Michel; Piot, Olivier (Analytical and bioanalytical chemistry, 2013)
Caffeine is utilised as a reference for permeation studies in dermatology and cosmetology. The present work aimed to monitor the permeation of a caffeine solution through the skin. For this purpose, Raman and infrared studies were performed. Raman microspectroscopy permitted a dynamic follow-up of the caffeine diffusion. In complementary, infrared microimaging provided information of the caffeine localization in the skin by applying multivariate statistical processing on skin tissue sections. Herein, we prove the possibility of tracking low concentrations of caffeine through the skin and we highlight some experimental limitations of vibrational spectroscopies.